Machine design - Wentzell, Timothy H. (Thomson Delmar Learning, 2004)
Electric motors and pneumatic and hydraulic drives are just a few of the topics examined by author Timothy Wentzell, a Professor of Mechanical Engineering Technology, in this straight forward introduction to machine design. A direct, logical approach strives to enhance basic understanding of the material by focusing on solving engineering design problems as opposed to working through extensive derivations. A broad collection of realistic examples and practical problems similar to those faced by working engineers encourages knowledge in the field of machine design. For this reason, the book is also usable by future and practicing engineers as a helpful reference.